2017
DOI: 10.1111/deci.12280
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Integration and Team Effectiveness: A Team Goal Orientation Approach

Abstract: Knowledge integration is critical to achieving both objective and subjective team effectiveness goals. Integrating knowledge resources, however, is a challenging activity for teams. Converging the theories of team goal orientation and knowledge integration, in this study we examine how team goal orientation impacts a team's internal knowledge integration, and how knowledge integration, in turn, affects multiple dimensions of team effectiveness. Data were collected from 90 self‐directed teams engaged in an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 103 publications
(231 reference statements)
2
35
0
1
Order By: Relevance
“…The results of these hypotheses are also consistent with the previous studies. The team outcomes mainly depend on the level of information exchange among the members (Guan, Xie, & Huan, 2018;Mehta, & Mehta, 2018). It is also reported that the interaction among all the members can be termed as the climate of the organization, and research suggests that climate is very much responsible for the general outcomes, i.e., trust, creativity or innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these hypotheses are also consistent with the previous studies. The team outcomes mainly depend on the level of information exchange among the members (Guan, Xie, & Huan, 2018;Mehta, & Mehta, 2018). It is also reported that the interaction among all the members can be termed as the climate of the organization, and research suggests that climate is very much responsible for the general outcomes, i.e., trust, creativity or innovation.…”
Section: Discussionmentioning
confidence: 99%
“…The team learning goals can be taken as the urge to learn new things, gaining positive outcomes, to compete and outperform the other teams and to avoid the failure in the projects (Bunderson & Sutcliff, 2003;Mehta & Mehta, 2018). The information exchange is the exchange of ideas, thoughts, knowledge and other work related information among organizational members (Johnson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the best way to approach emergency response tasks is vital and improving the performance in emergency management depends to a greater extent the ability of managers, volunteers and staff teams to coordinate and share their knowledge and information. Previous studies confirm that the biggest problem faced by organizations during a disaster in developing countries is the communication [14][15][16].…”
Section: Introductionmentioning
confidence: 87%
“…However, there are limitations in term of tools and theory that should be used by the teams in diverse organizations based on the emergency management success through knowledge integration as well as handling task [13]. Hence, few studies thus examined basic impact for integrating knowledge on both team efficiency and effectiveness [14]. Though, the investigation of knowledge integration and its relation to teamwork and team performance provide awareness to potentially support team and organizational learning efforts as well as reveals key issues in team training, yet, there are limitations in term of research conducted in this field [15].…”
Section: Introductionmentioning
confidence: 99%
“…Second, knowledge interaction can benefit the team members. Team members who participate in the knowledge interaction can not only get the rewards from the team leader after finishing the assignment, but also increase their individual creativity [41], and enrich their own experience [42]. Third, knowledge interaction can ensure the team's adaptive prevention.…”
Section: Knowledge Interaction and Sustainabilitymentioning
confidence: 99%